Eocene Gravity Flows in the Internal Prebetic (Betic Cordillera, SE Spain): A Vestige of an Ilerdian Lost Carbonate Platform in the South Iberian Margin - Josep Tosquella; Manuel Martín-Martín; Crina Miclăuș; José Enrique Tent-Manclús; Francisco Serrano; José Antonio Martín-Pérez (Geosciences)
In the Betic-Rif Cordilleras, recent works have evidenced the existence of well-developed Eocene (Ypresian-Bartonian) carbonate platforms rich in Larger Benthic Foraminifera (LBF). Contrarily to other sectors of the western Tethys, like the Pyrenean domain in the North Iberian Margin, where these platforms started in the early Ypresian (Ilerdian), in the Betic-Rif chains, the recorded Eocene platforms started in the late Ypresian (Cuisian) after a widespread gap of sedimentation including the Ilerdian time span. In this work, the Aspe-Terreros Prebetic section (External Betic Zone) is studied. An Eocene succession with gravity flow deposits consisting of terrigenous and bioclastic turbidites, as well as olistostromes with olistoliths, was detected. In one of these turbidites, we dated (with the inherent limitations when dating bioclasts contained by gravity flow deposits) the middle Ilerdian, on the basis of LBF, representing a vestige of a missing Illerdian carbonate platform. The microfacies of these turbidites and olistoliths rich in LBF have been described and documented in detail. The gap in the sedimentary record and absence of Ilerdian platforms in the Betic-Rif Cordillera have been related to the so-called Eo-Alpine tectonics (Cretaceous to Paleogene) and sea-level variations contemporarily with the establishment of shallow marine realms in the margins of the western Tethys.